Europe, the Middle East, and the ‘Arab Spring’ – The Shattering of the Dream - Nagar, Nir Barkan (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
This article addresses relations between Europe and the countries of the Middle East and the implications of these relationships over the past two decades, through an examination of the events of the ‘Arab Spring.’ The Arab Spring refers to a chain of events that swept through the Arab countries from late 2010, characterized by demonstrations, violence, and civil war. This was sparked by resistance to tyrannical regimes and led to the fall of the rulers of Egypt, Tunisia, and Libya. However, Islamists were able to utilize the protesters, who sought democracy, an equal economy, and the elimination of governmental corruption, to further their ambitions. At that time, it was not clear what the new regimes would look like, but it was widely expected that Islamist elements would gain power. Europe responded positively to these events, in terms of declarations, policy, and physical involvement, from the fear that Islamist forces would take advantage of the outcomes of the protests, despite the fact that, for decades, there had been collaboration and friendly relations between Western nations and many of the overthrown tyrants. This policy of turning a blind eye to the lack of democracy and human rights violations in these countries, however, had been perceived by many as contrary to European values. On May 25, 2011, the European Union published a document admitting their failure to achieve political reforms in the neighboring Arab countries. Following the events of the Arab Spring, a new approach to strengthening the partnership between Europe and the Arab world was needed. The objectives of European policy towards the Muslim world include halting massive Muslim migration, reducing the influence of fundamentalist and radical Islam in the Middle East and among Muslims in Europe, and ensuring a supply of energy resources obtained from these countries. Meeting these challenges will be a significant step in the right direction.

Artykuł omawia stosunki między Europą i krajami Bliskiego Wschodu oraz konsekwencje tych relacji w ciągu ostatnich dwóch dekad, poprzez analizę „arabskiej wiosny”. Określenie „arabska wiosna” odnosi się do serii wydarzeń obejmujących demonstracje, przemoc i wojnę domową, które przetoczyły się przez kraje arabskie od końca 2010 r. Wywołane przez siły oporu wobec autorytarnych reżimów doprowadziły do upadku przywódców Egiptu, Tunezji i Libii. Protesty zwolenników demokracji, zrównoważonej gospodarki i likwidacji korupcji rządowej udało się jednak wykorzystać do swoich celów islamistom. Wprawdzie nie było wówczas jasne, jakie nowe reżimy przejmą władzę, ale powszechnie oczekiwano, że będą to siły islamistyczne. W kategoriach deklaracji, polityki i zaangażowania fizycznego Europa zareagowała na wydarzenia arabskiej wiosny pozytywnie w obawie, że wyniki protestów mogą zostać wykorzystane przez siły islamistyczne, mimo że przez dziesięciolecia państwa Zachodu łączyła z wieloma obalonymi tyranami współpraca i przyjazne stosunki. Polityka przymykania oka na brak demokracji i łamanie praw człowieka w tych krajach była jednak często postrzegana jako sprzeczna z wartościami europejskimi. W dniu 25 maja 2011 r. Unia Europejska opublikowała dokument przyznający, że nie udało jej się przeprowadzić reform politycznych w sąsiednich krajach arabskich. Po wydarzeniach arabskiej wiosny konieczne było wypracowanie nowego podejścia do wzmocnienia partnerstwa między Europą a światem arabskim. Cele europejskiej polityki wobec świata muzułmańskiego obejmują powstrzymanie masowej migracji muzułmańskiej, zmniejszenie wpływu fundamentalistycznego i radykalnego islamu na Bliskim Wschodzie, a także wśród muzułmanów w Europie, oraz zapewnienie dostaw surowców energetycznych z tych krajów. Sprostanie tym wyzwaniom będzie znaczącym krokiem we właściwym kierunku.
Europa, Bliski Wschód i „arabska wiosna” – zawiedzione nadzieje
Keywords: Europe; Middle East; Arab Spring; Europa; Bliski Wschód; Arabska Wiosna